HUBUNGAN KEBIASAAN OLAHRAGA DENGAN DISMENORE PRIMER PADA REMAJA PUTRI DI SMA NEGERI 04 BANDA ACEH TAHUN 2014 - Fithriany, Fithriany; Amelia, Ulfa (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2015)
Dismenorrhea is menstrual pain that is felt in the lower abdomen and radiates up into the pelvis that can interfere with daily activities. Regular exercise can reduce stress and fatigue that can indirectly reduce pain. Prevalence of dismenorrhea in Indonesia (2008) amounted to 64,25%, consisting of 54,89% primary dismenorrhea and 98,5% secondary dismenorrhea. The purpose of this study was to determine the relation of primary dismenorrhea with the regular exercise at Senior High School 04 Banda Aceh. This research conducted since April to July. This was analitic study by using Cross Sectional design. There were 307 students in grade 1 and 2 as the population and the sampling method used Purposive Sampling as 75 respondents. The proportion of respondents who do exercise regulary (37,3%) of 28 respondents and who do not exercise regulary (62,7%) as many as 47 respondents. The proportion of primary dismenorrhea which felt by respondents, 42,67% of respondents had mild pain (32 respondents), 36,0% of respondents had moderate pain (27 respondents) and 21,3% of respondents had severe pain (16 respondents). Chi-Square test was conducted as analysis method with p<0,05. The result of this research found that there was a relation of primary dismenorrhea with the regular exercise of students at Senior High School 04 Banda Aceh and obtained value p=0,043 (p<0,05).